MPS 04-07 SHORT AND MID-TERM OUTCOMES OF ACUTE MYOCARDIAL INFARCTION WITH ELEVATED SYSTOLIC BLOOD PRESSURE ON ADMISSION. (September 2016) - Kumagai, Naoto; Dohi, Kaoru; Sato, Yuichi; Masuda, Jun; Seko, Tetsuya; Kitamura, Tetsuya; Yamada, Norikazu; Kakimoto, Hitoshi; Kawasaki, Atsushi; Makino, Katsutoshi; Nishikawa, Hideo; Ito, Masaaki
Abstract : Objective: Although lower admission systolic blood pressure (SBP) has been established as a poor prognostic factor in patients with acute myocardial infarction (AMI), the impact of preserved admission SBP on short and mid-term outcomes has not been fully evaluated. Design and Method: From January 2013 to March 2015, 1281 consecutive patients with AMI were registered in Mie ACS Registry, a prospective, multicenter registry in Japan. We evaluated 1122 patients (mean age 68 ± 13 years, male 78%) except for 159 patients with admission SBP < 100 mmHg. Patients were divided into three groups according to admission SBP: 100–139 mmHg (normal admission SBP; NBP group, n = 612), 140–179 mmHg (moderately elevated admission SBP; MBP group, n = 419) and ≥180 mmHg (excessively elevated admission SBP; EBP group, n = 91). The clinical characteristics, 30-day and 1-yaer outcomes (follow-up rate 94.7%) were compared among the three groups. Results: The rate of primary percutaneous coronary intervention and the number of diseased coronary vessels were not significantly different among the three groups. The Killip classification and the peak creatine kinase values were lowest in the MBP group. Heart failure, arrhythmia, shock and multi-organ failure during hospitalization were most often in the NBP group, but myocardial rupture was no significant difference in the three groups. The 30-day cumulative mortality was trend to be high in the NBP group (6.5%, 3.3% and 4.4% for NBP, MBP and EBP group, respectively, Log-Rank P = 0.069), and 1-year cumulative mortality after hospital discharge was significantly high in NBP group (5.5%, 1.6% and 2.4% for NBP, MBP and EBP group, respectively, Log-Rank P = 0.007) than other two groups (Figure). Conclusions: Admission SBP of less than 140 mmHg can be a risk of hemodynamic instability during hospitalization and an indicator of poor outcomes after hospital discharge in patients with AMI and preserved admission SBP.